Correlation between Atherogenic Index of Plasma and Various Domains of Cognitive Function in Type 2 Diabetes Mellitus Patients - Fasihah Irfani Fitri; Pahala Simanjuntak (Jurnal Kedokteran Brawijaya, 2023)
Cognitive impairment in patients with Type 2 Diabetes Mellitus (T2DM) is related to the lack of blood supply to the brain. Previous studies showed that the atherogenic index of plasma (AIP) is a predictor of vascular abnormalities, but studies investigating its association with cognitive functions in T2DM patients younger than 60 years remain limited. This study aimed to determine the correlation between AIP and various domains of cognitive function in T2DM patients. This study was a cross-sectional study involving 75 T2DM patients selected using a consecutive sampling technique at Haji Adam Malik General Hospital Medan from July 2021 to January 2022. Cognitive function was examined using the Visual Cognitive Assessment Test Indonesian Version (VCAT-INA) on several cognition domains. The AIP value of each patient was measured and categorized into high (AIP>0.21), intermediate (AIP between >0.11 and ≤0.21), or low (≤0.11). The mean triglyceride level was 176±108.3mg/dl, the HDL-C level was 38.3±12.1mg/dl, and the mean AIP value was 0.191±0.25. The mean score of the VCAT-INA was 21.7±2.3, which was lower than normal. The AIP value showed significant negative correlation with global cognition (r=0.432, p<0.001) and various cognitive domains, namely memory (r=-0.375, p=0.001), attention (r=-0.383, p=0.001), executive function (r=-0.051, p=0.663), visuospatial (r=-0.306, p=0.008), and language (r=-0.352, p=0.002). In short, there is a significant correlation between AIP value and domains of cognitive function, such as memory, attention, visuospatial, and language domains, but not with executive domains.